The Differential and Dynamic Progression of Hepatic Inflammation and Immune Responses During Liver Fibrosis Induced by Schistosoma japonicum or Carbon Tetrachloride in Mice - Song, Li-Jun; Yin, Xu-Ren; Mu, Sha-Sha; Li, Jia-Huang; Gao, Hong; Zhang, Ying; Dong, Pan-Pan; Mei, Cong-Jin; Hua, Zi-Chun (Frontiers in Immunology, 2020)
Liver fibrosis can result from various causes and could progress to cirrhosis and cancer; however, there are no effective treatments due to that its molecular mechanism is unclear. liver fibrosis model made by Schistosoma japonicum (S. japonicum) infection or Carbon tetrachloride (CCl4) intraperitoneal injection is a conventional model used in liver fibrosis-related studies for mechanism or pharmaceutical research purposes. But the differences in the pathological progression, immune responses and the underlying mechanism between the two liver fibrosis models have not been carefully compared and characterized, which hinders us from correctly understanding and making better use of the two models. In the present study, the pathological changes to the liver, and the cytokines, inflammatory factors, macrophages, and lymphocytes subsets involved were analyzed in both liver fibrosis models of S. japonicum infection and CCl4 intraperitoneal injection. Additionally, the pathological progression, immune responses and the underlying injury mechanism in these two models were compared and characterized. The results showed that the changing trend of interleukin-13 (IL-13), transforming growth factor beta (TGF-β), inflammatory factors, and M1, M2 macrophages, were consistent with the development trend of fibrosis regardless of whether liver fibrosis was caused by S. japonicum or CCl4. For lymphocyte subsets, the proportions of CD3+ T cells and CD4+ T cells decreased gradually, while proportion of CD8+ T cells peaked at 6 weeks in mice infected with S. japonicum and at 12 weeks in mice injected with CCl4. With prolonged S. japonicum infection time, Th1 (CD4+IFN-γ+) immunity converted to Th2 (CD4+IL-4+) / Th17 (CD4+IL-17+) with weaker regulatory T cell (Treg) (CD4+CD25+FOXP3+) immunity. However, in liver fibrosis caused by CCl4, Th1 cells occupied the dominant position, while proportions of Th2, Th17, and Treg cells decreased gradually. In conclusion, liver fibrosis was a complex pathological process that was regulated by a series of cytokines and immune cells. The pathological progressions and immune responses to S. japonicum and CCl4 induced liver fibrosis were different, possibly because of their different injury mechanisms. The appropriate animal model should be selected according to the needs of different experiments and the pathogenic factors of liver fibrosis in the study.